2015
DOI: 10.1063/1.4916028
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed Al-chelated gelatin for highly transparent non-volatile memory applications

Abstract: Using the biomaterial of Al-chelated gelatin (ACG) prepared by sol-gel method in the ITO/ACG/ITO structure, a highly transparent resistive random access memory (RRAM) was obtained. The transmittance of the fabricated device is approximately 83% at 550 nm while that of Al/gelatin/ITO is opaque. As to the ITO/gelatin/ITO RRAM, no resistive switching behavior can be seen. The ITO/ACG/ITO RRAM shows high ON/OFF current ratio (>105), low operation voltage, good uniformity, and retention characteristics at ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 17 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…On the other hand, with the ever-increasing concerns for healthcare, medicine and environments, the development of biocompatible, biodegradable and environmentally friendly electronics, the so-called green electronics, has become a pressing issue and a hot research topic for both academia and industry [9,10]. Owing to the merits of wide availability, flexibility, printable capability, and easy process and low cost [11,12], many types of biomaterials, such as DNA [13], protein [10,14,15], nucleobases [16], paper [17,18] and gelatin [19,20], have been explored for the fabrication of various green electronic devices, as well as memristors with the simple Metal-Insulator-Metal (MIM) sandwich structure [20]. We have also demonstrated a type of biocompatible transitional memristors using soluble albumen dielectric layer and tungsten (W) and magnesium (Mg) as the electrodes [13], and showed their potential for transitional implants or medical application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, with the ever-increasing concerns for healthcare, medicine and environments, the development of biocompatible, biodegradable and environmentally friendly electronics, the so-called green electronics, has become a pressing issue and a hot research topic for both academia and industry [9,10]. Owing to the merits of wide availability, flexibility, printable capability, and easy process and low cost [11,12], many types of biomaterials, such as DNA [13], protein [10,14,15], nucleobases [16], paper [17,18] and gelatin [19,20], have been explored for the fabrication of various green electronic devices, as well as memristors with the simple Metal-Insulator-Metal (MIM) sandwich structure [20]. We have also demonstrated a type of biocompatible transitional memristors using soluble albumen dielectric layer and tungsten (W) and magnesium (Mg) as the electrodes [13], and showed their potential for transitional implants or medical application.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin is a biomaterial obtained from animal skins, bones etc, and it has a quasi-reversible water dissolving property [21]. Recent work has shown that gelatin could be a suitable dielectric material for the fabrication of memristors with good properties [19,20], but very limited work has been done for in-depth understanding of the device properties and process influence, and more work is needed before its application. The working mechanism of the devices is still not clear, and the repeatability, reliability and stability of the devices are yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The device was first activated by applying a positive bias voltage of 5 V with a compliance current of 2 mA, then sweeping the device around 5 V to −5 V to reset the device at −2 V and set it at 2.1 V. Whereas, the device without ZNs that set at 3.9 V and reset at −3.5 V. Thus, lower operating voltage realized in Al/GOZNs/ITOPET due to the embedded ZNs [228]. [205], [237]- [252]. But, ZnO is attractive to many optoelectronic processes, also possesses a high absorption rate in the ultraviolet (UV) range.…”
Section: F Transparent/flexible Zno Based Rrammentioning
confidence: 99%
“…Some proteins such as silk fibroin (SF), ferritin, keratin, and collagen have been developed as data storage memory devices and neuromorphic devices. [ 59–103 ]…”
Section: Introductionmentioning
confidence: 99%